Carcinoid heart disease: a remarkable recovery. Issue 6 (2nd November 2015) - Proesmans, S.; Van fraeyenhove, F.; Dossche, K.; Mattelaer, C.; Scott, B.
Abstract : A 65-year-old female patient with metastatic neuroendocrine tumour of the small intestine developed carcinoid valve disease and intractable right heart failure. She underwent successful cardiac valve replacement of both tricuspid and pulmonary valves. One year after surgery, she has regained full functional capacity.